Nepal : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that Nepal's real GDP growth is estimated to have slowed to 0.8 percent in 2001/02 from 5 percent in the previous year (fiscal year ending mid-July). Agricultural growth slowed to less than 2 percent from more than 4 percent, reflecting irregular rainfall. The output of nonagricultural sectors was largely stagnant, with manufacturing and tourism sectors particularly hit hard by the domestic security situation as well as the global slowdown. Inflation was subdued at about 3 percent, reflecting weak domestic demand and stable Indian prices for most of the year.